Association of ACE2 gene functional variants with gestational diabetes mellitus risk in a southern Chinese population - Huang, Gongchen; Liang, Qiulian; Wang, Yukun; Qin, Linyuan; Yang, Haili; Lin, Lin; Yu, Xiangyuan (Frontiers in Endocrinology, 2022)
Objective To explore the relationship between angiotensin-converting enzyme 2 (ACE2) genetic variants and gestational diabetes mellitus (GDM) in a southern Chinese population. Methods Potential functional variants (rs2106809, rs6632677, and rs2074192) of ACE2 were selected and genotyped in 566 GDM patients and 710 normal pregnaõncies in Guilin, China. The odds ratio (OR) and its corresponding 95% confidence interval (CI) were used to evaluate the association between genetic variant and GDM risk, and then the false positive report probability, multifactor dimensional reduction (MDR), and bioinformatics tools were used to confirm the significant association in the study. Results After adjusting for age and prepregnancy body mass index, logistic regression analysis showed that ACE2 rs6632677 was significantly associated with a decreased risk of GDM (CC vs. GG: adjusted OR = 0.09, 95% CI: 0.01 – 0.71, P = .023; GC/CC vs. GG: adjusted OR = 0.68, 95% CI = 0.46 – 0.99, P = .048; and CC vs. GG/GC: adjusted OR = 0.09, 95% CI = 0.01 – 0.72, P = .024), whereas rs2074192 was associated with increased GDM risk (TT vs. CC/CT: adjusted OR = 1.38, 95% CI = 1.08 – 1.75, P = .009). Furthermore, we found that rs6632677 interacted with SBP (Pinteraction = .043) and FPG (Pinteraction = .021) and rs2074192 interacted with HDL-c (Pinteraction = .029) and LDL-c (Pinteraction = .035) to influence the GDM risk of the individual. In the MDR analysis, the rs6632677 was the best one-locus model, and the three-loci model was the best interaction model to predict GDM risk. In addition, functional analysis confirmed that rs2074192 may regulate the splicing process of ACE2 gene. Conclusion ACE2 gene variants are significantly associated with the risk of GDM via gene–gene and gene–environment combinations. The rs2074192 C > T affects the splicing of the ACE2 gene, which may be a potential mechanism leading to the changed susceptibility of an individual female during pregnancy to GDM.